Pengaruh Self Efficacy, Pendidikan Kewirausahaan, dan Lingkungan Teman Sebaya Terhadap Minat Berwirausaha - Linda Jukda Tunisa; Kusmuriyanto; Jarot Tri Wibowo Santoso (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
The purpose of this study was to analyze the effect of self-efficacy, entrepreneurship education, and peer environment on entrepreneurial interest in SMK Hasyim Asy'ari Bojong students simultaneously or partially. The research population was Hasyim Asy'ari Vocational High School students as many as 133 students. This study is a population study using a saturated sample. Data collection with questionnaires and documentation. The data analysis technique used descriptive analysis. The results of the multiple regression analysis of this study are Y = 8,250 + 0,543X1 + 0,213X2 + 0,689X3 + e. There is a simultaneous effect of 64.4%, while partially self- efficacy is 15.13%, entrepreneurship education is 1.10%, and peer environment is 19.27%. The conclusion in this study is that there is a simultaneous influence of self-efficacy, entrepreneurship education, and peer environment on interest in entrepreneurship. Partially, only self-efficacy and peer environment have a positive effect on interest in entrepreneurship, while entrepreneurship education does not have a positive effect on interest in entrepreneurship.